Pengaruh Penambahan Abu Tandan Kelapa Sawit Terhadap Daya Dukung Tanah Lempung - Sendi Fitramsya; Elly Tri Pujiastutie (MAJALAH TEKNIK SIMES, 2022)
ABSTRACT One of the most important material that has great impat to a structure or onstrution in civil engineering job is soil, either that job is building or road pavement construction. One of problem which may happen faced by consultant or contractor ( especially for road pavement construction ) is take care of soil and other bad component to make sure those components can be used as ingredient for that pavement construction. Thing can be done to fix the mechanic property in this research is by using chemical way like adding oil palm ‘s stem ashes with 0%, 6,5%, 7%, 8%, and 8,5 % variation from clay. Biggest CBR value happen when 0,2 penetration with CBR value was 18,078% by using 8,5 % oil palm’s stem addictive. This value has increased by 2,288 % from the CBR value from the original soil which is 15,790%. With adding 6,5% oil palm’s stem ashes the CBR value increased 0,703%, when adding 7% increased by 0,273% and also when adding 8% increased 1,168%. This CBR value qualified Bina Marga 2018 general specification ( Third revision ) where CBR value > 6%.